FOREIGN EXPERIENCE IN COMBATING FORCED LABOR: PROBLEMS AND SOLUTIONS (Scientific journal of the Fergana State University, 2026)
In the global community, the socio-economic and cultural factors that contribute to the widespread use of forced labor, as well as poverty, lack of education, migration and the ongoing reforms to combat the exploitation of the informal labor sector, have become a pressing problem of governance. Strategies are being developed to prevent and combat forced labor. In society, these processes have been assessed at the political level by foreign countries.